Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Peserta Didik SMA 1 Cawang Baru - Damayanti, Dinda Rosa; Raihan, Raihan; Ulfah, Maria (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2024)
This research aims to determine whether there is an influence of the use of the mind mapping learning model on student learning outcomes at SMA 1 Cawang Baru and to measure how much influence the use of the mind mapping learning model has on student learning outcomes. The research approach used is quantitative with the correlation regression method. The object of this research is class X students of SMA 1 Cawang Baru. The population in this study was 40 students, with data collection techniques using saturated samples so that the entire population of 40 students was the sample in this study. Meanwhile, analyzing the data uses the product moment correlation formula (and hypothesis testing (t test). The results of this research conclude that there is an influence between the use of the mind mapping learning model on the learning outcomes of students at SMA 1 Cawang Baru with R = 0.326 and R^2 = 0.106. This means that the mind mapping learning model has a positive and significant influence on the learning outcomes of students in class X SMA 1 Cawang Baru.